Indonesian Export of Footwear Product: Export Destination Countries Analysis - Siti Hodijah; Yohanes Vyn Amzar; Thereza Ismiranda (JEJAK: Jurnal Ekonomi dan Kebijakan, 2022)
This study aims to analyze factors affecting the export volume of Indonesian footwear products in eight export destination countries during the 2017-2020 period. The independent variables used in the study were Export Price, Real Gdp of Export Destination Countries, Population of Export Destination Countries, Exchange Rates, and Export Growth of Tiongkok Footwear. In contrast, the dependent variables were the export volume of Indonesian footwear. The study used multiple linear regression analysis with panel data. Based on the study's results, the variable export price negatively and significantly affects the volume of Indonesian footwear exports. In contrast, the variable real GDP and growth of Tiongkok footwear exports positively and significantly influence the volume of Indonesian footwear export exports. In contrast, the variable population of the destination country of footwear exports and exchange rates does not significantly affect the volume of Indonesian footwear exports in Indonesia's eight export destination countries.